BIOPROSPECTING NEGLECTED BOTANICALS AS PHYTO-FERTILIZER FOR UNDERUTILIZED FOOD CROPS - Abiala, Moses Akindele (Journal of Agricultural Sciences (Belgrade), 2019)
Botanicals are part of the bioresources for sustainable growth of food crops, however some botanicals have been neglected. This study investigates the potential effects of neglected botanicals on selected underutilized food crops (millet, sorghum and sesame) in Nigeria. Blotter technique and soil inoculation methods were used to evaluate the best botanicals that could be employed to enhance seed germination (SG) and seedling growth of underutilized food crops. With the exception of Newbouldia laevis, other botanicals enhanced seed germination of all tested crops. Ficus asperifolia and Parquetina nigrescens significantly (p
Keywords: Fertilizer; Seeds; Seedlings; Germination; Foods; Food crops; Crops